Tumor-Treating Fields for the treatment of glioblastoma: a systematic review and meta-analysis. Issue 4 (20th April 2021) - Regev, Ohad; Merkin, Vladimir; Blumenthal, Deborah T; Melamed, Israel; Kaisman-Elbaz, Tehila
Abstract: Background: Tumor-Treating Fields (TTFields) is an emerging treatment modality for glioblastoma (GBM). Studies have shown a good safety profile alongside improved efficacy in newly diagnosed GBM (ndGBM), while a less clear effect was shown for recurrent GBM (rGBM). Despite regulatory support, sectors of the neuro-oncology community have been reluctant to accept it as part of the standard treatment protocol. To establish an objective understanding of TTFields' mechanism of action, safety, efficacy, and economical implications, we conducted a systematic literature review and meta-analysis. Methods: A systematic search was conducted in PubMed, Scopus, and Cochrane databases. Twenty studies met the pre-defined inclusion criteria, incorporating 1636 patients (542 ndGBM and 1094 rGBM), and 11 558 patients (6403 ndGBM and 5155 rGBM) analyzed for the clinical outcomes and safety endpoints, respectively. Results: This study demonstrated improved clinical efficacy and a good safety profile of TTFields. For ndGBM, pooled median overall survival (OS) and progression-free survival (PFS) were 21.7 (95%CI = 19.6-23.8) and 7.2 (95%CI = 6.1-8.2) months, respectively. For rGBM, pooled median OS and PFS were 10.3 (95%CI = 8.3-12.8) and 5.7 (95%CI = 2.8-10) months, respectively. Compliance of ≥75% was associated with an improved OS and the predominant adverse events were dermatologic, with a pooled prevalence of 38.4% (95%CI = 32.3-44.9). Preclinical studies demonstrated TTFields' diverse molecular mechanism of action, its potential synergistic efficacy, and suggest possible benefits for certain populations. Conclusions: This study supports the use of TTFields for GBM, alongside the standard-of-care treatment protocol, and provides a practical summary, discussing the current clinical and preclinical aspects of the treatment and their implication on the disease course.